(untitled) (Research, Society and Development, 2021)
Every year, in Brazil, about one hundred thousand accidents with venomous animals occur, resulting in approximately two hundred and twenty deaths. The main animals involved are scorpions, spiders, bees, wasps and snakes. Frequency is determined by different factors such as temperature, humidity, rainfall, ecological imbalance, expansion of urban and agricultural areas. Children are more vulnerable due to their inherent curiosity, added to the lack of risk and the condition of the immune system, which is still in formation, which enhances gravity. This study analyzed the epidemiological profile of pediatric accidents involving venomous animals in the municipality of Chapecó, SC, from 2014 to 2018. Method: Retrospective study of accidents involving venomous animals registered in the Epidemiological Surveillance Notification Disease Information System. Of the 489 notifications recorded, the spiders caused 24.34%. In 2014, 177 cases were reported, approximately one case every two days, the year with the highest incidence. The months of January and February were more significant by the total number of notifications. Limbs extremities were the hardest hit. The male gender was the most affected (55%). The highest frequency occurred in urban areas (79.8%). There were no deaths. The municipality of Chapecó reveals a high incidence of accidents with venomous animals, showing the need to establish services and campaigns about the risk, especially in the months with higher temperatures. With an emphasis on local reality, it is important that the population be alerted and precautions taken, especially with children.